Preparation of cross‐linked porous starch and its adsorption for chromium (VI) in tannery wastewater. (5th June 2015) - Hu, Jing; Tian, Ting; Xiao, Zuobin
<x xml:space="preserve">Abstract</x> Various cross‐linked amino starches were used for chromium (VI) adsorption in the environmental protection area. In order to improve chromium (VI) adsorption, the new cross‐linked amino starch with porous structure (CPS) was synthesized by reverse emulsion polymerization, using waxy corn starch after enzyme hydrolysis (ES) as raw material, N, N′‐methylene‐bis‐acrylamide (MBAA) as cross‐linking agent, and ceric ammonium nitrate as initiator. The effects of the volume ratio of oil phase/aqueous phase, the content of emulsifiers, ES, and MBAA on the swelling, solubility property, chromium (VI) adsorption capacity, grafting ratio, and conversion ratio of CPS were investigated. The properties and morphology of CPS have been characterized by Fourier transform infrared spectroscopy, thermal gravimetric analysis, differential scanning calorimetry, and scanning electron microscopy. The maximum adsorption capacity for chromium (VI) ions of CPS reached 28.83 mg/g when the synthesis condition of CPS was controlled as Voil: VH2O 8:1, emulsifier 9%, starch 2%, and MBAA 10%. The new adsorption peaks of CPS at 1641 cm−1 and 1541 cm−1 proved the cross‐linking reaction between ES and MBAA. The thermal decomposition temperature of CPS was improved to 250°C, and the gelatinization temperature and enthalpy value of CPS were decreased compared with ES because of the occurrence of the cross‐linking reaction. The CPS was like a sponge with a large amount of pores, and the size of these pores was 5 µm. CPS also exhibited superior adsorption property to other heavy metal ions such as cadmium (II) and lead (II) (17.37 and 35.56 mg/g). Copyright © 2015 John Wiley & Sons, Ltd.